Mexico and Peru rural poverty evolution under the context of deterioration in Latin America and the Covid-19 pandemic - Sánchez-Alcalde, Luis (2022)
In the present study, Mexico and Peru (two Latin American countries with similar rural and historical characteristics) were analyzed in order to determine the relationship between the rural poverty rate and factors associated with it; this in the context of the growth of poverty in the region, a trend that was noted before the Covid-19 pandemic. Based on ECLAC data, on the one hand, the results made it possible to observe that Mexico obtained a higher average rural poverty rate than Peru, even higher than the region, but with less dispersion over time. On the other hand, it was observed that in the Mexican and Peruvian cases, rural poverty is positively associated with the employed population in agriculture, while it is negatively associated with the rate of school attendance. Likewise, for Peru, a negative and significant correlation was observed with access to public water services and public sector social spending. These characteristics allowed us to conclude and recommend that the increase in rural poverty in these countries, caused by the deterioration in the region and the effects of the pandemic, can be mitigated through employment, education and social spending policies or programs in general, particularly in-housing infrastructure. In the same way, it was recommended to pay attention to the field since it seems that the problems in the region will become more acute because of food security and climate change.